Complementary Strategy for Regioselective Synthesis of Diverse β-Hydroxysulfones from Thiosulfonates - Son, Soobin; Shyam, Pranab K.; Park, Hyowon; Jeong, Ilgyo; Jang, Hye Young (European Journal of Organic Chemistry, 2018)
The regioselective synthesis of variously substituted β-hydroxysulfones from thiosulfonates was developed. The reactions of thiosulfonates and alkenes via a peroxy radical intermediate provided 2° and 3° β-hydroxysulfones in good yields. The presence of epoxides instead of alkenes changed the reaction mechanism to nucleophilic addition involving sulfinate anions to afford 1° and 2° β-hydroxysulfones. By using both protocols, the regiochemical outcome of the β-hydroxysulfones synthesized from thiosulfonates was diversified.
Keywords: Radical reactions; Reaction mechanisms; Sulfones; Sulfonylation; Synthesis design